Diagnostic disparities in inborn errors of immunity: From clinical suspicion to diagnosis - Karen M. Gilbert, PhD; Robert F. LeCates, MA; Alison A. Galbraith, MD, MPH; Paul J. Maglione, MD, PhD; Stephanie Argetsinger, MPH; Nicholas L. Rider, DO; Jocelyn R. Farmer, MD, PhD; Mei-Sing Ong, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Emerging evidence suggests that inborn errors of immunity (IEI) are underdiagnosed among underserved populations. However, there remains a lack of national studies evaluating diagnostic disparities in IEI. Objective: We examined disparities in the timely IEI diagnosis and related health outcomes. Methods: A retrospective analysis was performed of a US national claims database (years 2007 to 2021). Participants included patients diagnosed with an “unspecified immune deficiency” (uID) and presented with IEI-related symptoms, who later received an IEI diagnosis (n = 1429). We quantified the diagnostic interval from clinical suspicion (uID) to IEI diagnosis and examined its association with sociodemographic factors and related health outcomes. Results: The median (interquartile range) diagnostic interval was 369 (126-808) days. Diagnostic interval was 14% longer among patients residing in predominantly non-White neighborhoods, compared with those in predominantly White neighborhoods (P = .04), despite having more severe IEI-related symptoms at uID diagnosis and significantly more health care encounters for pneumonia (incidence rate ratio, 2.24; 95% confidence interval, 1.40-3.70) and sepsis (incidence rate ratio, 2.15; 95% confidence interval, 1.21-3.99) in the year after uID diagnosis. Residence in neighborhoods with greater deprivation was also associated with more severe IEI-related symptoms and greater health care utilization in the year after uID diagnosis. Older age was associated with longer diagnostic interval (P < .001). Longer diagnostic interval was associated with a longer interval to receiving IgR therapy (hazard ratio, 0.64; 95% confidence interval, 0.49-0.83). Conclusion: We observed significant racial and socioeconomic disparities in the timeliness of IEI diagnosis and IEI-related outcomes. Further studies are needed to address the underlying factors contributing to diagnostic inequity.